Strategic Human Resource Management And Organizational Performance: An Investigation Of Profit-Oriented Companies In Zambia - Mwambela, Able (Journal of Business and Management Review, 2024)
Research Aims:  The study aims to investigate the correlation between SHRM practices such as incentives and rewards, formal performance appraisal, recruitment and selection, career development, and organizational development with measures of organizational performance, including revenue growth rate, return on equity, return on assets, and profitability Design/methodology/approach: Human resources play a vital role in achieving organisational performance.  A study on 169 profit-making organisations in Zambia examined the impact of different Strategic Human Resource Management (SHRM) components on performance.  A quantitative approach was used, and the questionnaire was divided into three parts. A stratified random sample of 169 organisations' managers was studied.  Research Findings: According to the results, managers highly recommended Incentives, Rewards, recruitment, and Selection to achieve excellence.  Formal Performance Appraisal received moderate evaluation, while Career Development received the least.  The study concluded that SHRM components affect organisational performance regarding revenue growth rate, return on equity, return on assets, and profitability (p < 0.01).  The study recommended aligning the SHRM strategy with other activities to improve performance, focusing on recruitment.  Integrating HR practices with overall strategies can bring numerous benefits to organisations.  By aligning these two critical components, companies can ensure that their human resources are being utilised effectively and efficiently.  Theoretical Contribution/Originality : The study provides evidence that specific SHRM components, such as incentives and rewards, formal performance appraisal, and recruitment and selection, positively correlate with organizational performance measures like revenue growth rate, return on equity, and return on assets. This research contributes to the existing literature by highlighting the importance of integrating HR practices with overall strategies to enhance organizational performance, particularly in the Zambian profit-oriented sector. Keywords: Strategic Human Resource Management, Integration, Performance